Initiation and maintenance of lifestyle changes among participants in a healthy life centre: a qualitative study - Cille H. Sevild; Christopher P. Niemiec; Lars Edvin Bru; Sindre M. Dyrstad; Anne Marie Lunde Husebø (BMC, 2020)
Abstract Background Since the early 2000s, Healthy Life Centres have been established in Norway to promote physical and mental health. Yet to date, little is known about the efficacy of Healthy Life Centres in promoting health behaviour change and maintenance or the factors that underlie these processes. Accordingly, the aim of the current study was to examine the factors that participants in a Healthy Life Centre perceive as relevant for the initiation and maintenance of lifestyle changes toward more physical activity and consumption of a healthier diet. Method Participants were purposely recruited from among adherers in a 12-month multi-method research project at a Healthy Life Centre. Individual, semi-structured interviews were conducted with 8 women and 6 men who were between the ages of 20 and 61 years old. Data were analysed using Systematic Text Condensation. Results Three main themes were derived from this analysis. The first theme focused on the motives behind initiation and maintenance of lifestyle changes along with the importance of a relationally supportive environment to promote perceived competence in pursuing a healthy lifestyle. The second theme focused on strategies for coping with the challenges and potential pitfalls that were associated with various unpleasant experiences and life events. The third theme focused on several specific skills that were helpful to the initiation and maintenance of lifestyle changes. Conclusion The current study enhanced an understanding of the initiation and maintenance of lifestyle changes, although these processes were not disentangled in participants' experiences. In line with self-determination theory, the results suggested that lifestyle change is more likely to be initiated and maintained when goals are not only achievable but also regulated with autonomous motivation and of intrinsic value. Conversely, lifestyle change is difficult to maintain when motives are external to the self. Further, cognitive and behavioural skills were valuable and necessary in coping with unpleasant emotions. Finally, the critical function of self-regulation skills for making realistic plans and prioritizations in order to balance healthy lifestyle behaviours with the routines of "daily life" while monitoring outcomes was readily apparent. Healthy Life Centres can contribute to these processes in meaningful ways.